Buckling capacities of Double-T-Box Girders – A numerical approach. (December 2021) - Deepak, M.S.; Beulah Gnana Ananthi, G.
Abstract: Owing to the increase in the applications of the built-up Cold-Formed Steel (CFS) sections in the construction industry, there exists an immediate demand in standardisation of the design rules to use built-up sections as structural members. This paper presents a numerical approach to estimate the capacities and structural buckling behaviour of mono-symmetric stiffened built-up CFS homogeneous and Hybrid Double-T-Box Girders (DTBGs and HDTBGs) subjected to uniform static flexure. The geometry of these built-up sections is unique and has the combined advantages of an open 'T' section girder that offers greater resistance against flexural buckling moment and a closed box region, which resist against lateral-torsional bucking. A verified and validated Finite Element Analysis (FEA) parametric study on 120 ideal FE models of I-DTBGs and I-HDTBGs are performed using ABAQUS software. The overall non-dimensional member slenderness (λLT ) considered in this study is ranging up to 1.80. This study captured the three primary modes of failures: local, distortional and lateral-torsional buckling and two interaction modes of failures viz, local plus distortional and distortional plus lateral buckling and their sub kinds. For, the DTBGs and HDTBGs with λLT <0.4 say in short to medium span local and distortional buckling is predominant and in the case of larger span girders of with λLT >0.4 exhibits lateral buckling failure. The bending capacities of the girders and their varying buckling modes are dependent upon the increase of member slenderness and plate element stiffness. The obtained flexural capacities of these girders from FEA have been compared against the Effective Width Method (EWM) design equations as suggested in Eurocode standards. This research study identifies that there exist notable differences while assessing the buckling capacities of these DTBGs and HDTBGs using the existing design rules and their relationships. Henceforward, a new simplified and appropriate design equation is formulated, and its corresponding buckling curve is illustrated in this study. The arrived equation is, χLT = 0.13 λ 2 LT − 0.65 λLT + 1.11 that is also found to be satisfactory as per reliability analysis.